NMR-based metabolomics for simultaneously evaluating multiple determinants of primary beef quality in Japanese Black cattle - Yoshinori Kodani (Nature Portfolio, 2017)
Abstract Analytical methodologies to comprehensively evaluate beef quality are increasingly needed to accelerate improvement in both breeding and post-mortem processing. Consumer palatability towards beef is generally attributed to tenderness, flavor, and/or juiciness. These primary qualities are modified by post-mortem aging and the crude content and fatty acid composition of intramuscular fat. In this study, we report a nuclear magnetic resonance (NMR)-based metabolic profiles of Japanese Black cattle to evaluate the compositional attributes of intramuscular fat and the long-term post-mortem aging. The unsaturation degree of triacylglycerol was estimated by the 1H NMR spectra and was correlated with the content ratio of unsaturated fatty acids (R 2 = 0.944) and the melting point of intramuscular fat (R 2 = 0.871). NMR-detected profiles of water-soluble metabolites revealed overall metabolic change (R 2 = 0.951) and several metabolites (R 2 > 0.818) linearly correlated with long-term aging duration, which can be used to evaluate the aging rate and aging duration of beef. This approach also provided the pH profile during aging, which is related to the water-holding capacity of beef. Thus, NMR-based metabolomics has the potential to evaluate multiple parameters related to the beef qualities of Japanese Black cattle.